Human Umbilical Cord Blood Mononuclear Cells Ameliorate CCl4-Induced Acute Liver Injury in Mice via Inhibiting Inflammatory Responses and Upregulating Peripheral Interleukin-22 - Zhang, Jinming; Zhai, Hengben; Yu, Pei; Shang, Dabao; Mo, Ruidong; Li, Ziqiang; Wang, Xiaolin; Lu, Jie; Xie, Qing; Xiang, Xiaogang (Frontiers in Pharmacology, 2022)
(1) Background: Human umbilical cord blood mononuclear cells (hUCBMNCs) show therapeutic effects on many inflammatory diseases. The deterioration of acute liver injury attributes to excessive inflammatory responses triggered by damage-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs). Whether hUCBMNCs is a promising strategy for acute liver injury/failure needs to be investigated. (2) Methods: Liver injury mice induced by PAMPs, DAMPs or DAMPs plus PAMPs were developed. DAMPs included CCl4 (carbon tetrachloride), APAP (acetaminophen), and ConA (Concanavalin A). PAMPs included Klebsiella pneumoniae (K.P.) and Salmonella typhimurium (S. Typhimurium). DAMPs plus PAMPs-induced liver injury were developed by sequential CCl4 and K.P. administration. hUCBMNCs were injected intravenously. (3) Results: hUCBMNCs significantly prolonged mice survival in DAMPs plus PaAMPs-induced liver failure but had no benefit in bacterial infection mice. hUCBMNCs significantly alleviated hepatic-necrosis post CCl4/ConA insult. In CCl4-induced acute liver injury, IL-22 were up-regulated and liver regeneration was enhanced after hUCBMNCs treatment at 48h. The levels of p62 and LC3B-II, autophagy markers, were also up-regulated in hUCBMNCs group. (4) Conclusion: hUCBMNCs as a kind of cell therapeutic strategy could attenuate acute liver injury in mice, which is executed by enhancing autophagy and regeneration in liver via inhibiting inflammatory responses and up-regulating peripheral IL-22.